The increasing role of contract research organizations in the evolution of the biopharmaceutical industry - Margherita Balconi; Valeria Lorenzi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2017)
The role played in the last decades by contract research organizations (CROs) has been almost completely neglected by the economic and managerial literature. At most they are presented as firms performing routine clinical tasks, a portrait which is largely outdated and misleading. Thus the main objective of this paper is to highlight the evolution of the CRO segment of the biopharma industry, discuss the foundations of CROs' comparative advantage and underline the consequences of their growth for the effective functioning of the industry. We suggest that the increased role acquired by CROs in performing fundamental phases of R&D has made the anatomy of the biopharma system more functional. In fact even if the turbulence and mortality of IP-based biotech firms is extremely high, if they rely to a great extent on CROs, the experience acquired to carry out their projects - which mostly fail - does not get lost but cumulatively enhances CROs' capabilities, a resource that can be tapped to carry out further projects.
Keywords: D83; L10; L22; O30; 330; Evolution of industries; R&D outsourcing; tacit knowledge; biopharma industry